Assessing the fraud prevention mechanisms in Malaysian government agencies / Tuan Zainun Tuan Mat ... [et al.] - Tuan Mat, Tuan Zainun; Syed Mustapha Nazri, Sharifah Nazatul Faiza; Mohd Fahmi, Fadzlina; Ismail, Aida Maria; Smith, Malcom (Accounting Research Institute & Faculty of Accountancy, 2013)
The public sector is most susceptible to fraud but effective prevention mechanisms will help it to minimize fraud risk. This paper provides an indicator on the effectiveness of fraud prevention mechanisms, which facilitate it to minimize the fraud risks, implemented by the public sector. The framework of this study is developed based on the fraud triangle concepts which explain how pressure, rationalization and opportunity could be minimized by implementing effective fraud prevention activities such as internal control assessments, training and education, and other organisation-wide strategies. This study concentrates on fraud training and education mechanisms. (Insert research method). The results show that raising fraud awareness activities, training in ethics or code of conduct, training in privacy principles and training to employees involved in fraud control activities are effective mechanisms for fraud prevention.